PENGARUH TOTAL ASSET TURNOVER DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PT ASTRA AGRO LESTARI TBK PERIODE 2012-2024 - Ayu Widia Asih; Hadijah Febriana (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) on Return on Equity (ROE) at PT Astra Agro Lestari. The data used in thisstudy are secondary data sourced from the financial statements available on the official website of PT Astra Agro Lestari Tbk for the period 2012–2024. The method employed in this research is a descriptive quantitative approach. The results of the study show that, partially (t-test), Total Asset Turnover (TATO) has a significant effect on Return on Equity (ROE), with a t-value of 4.041 > t-table value of 2.228 and a significance level of 0.002 < 0.05. Meanwhile, Debt to Equity Ratio (DER) does not have a significant partial effect on Return on Equity (ROE), with a t value of 0.985 < 2.228 and a significance level of 0.348 > 0.05. The results of the simultaneous test (Ftest) indicate that Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) jointly have a significant effect on Return on Equity (ROE), with an F-value of 8.179 > F-table value of 4.10 and a significance level of 0.008 < 0.05